Musculoskeletal Disorders in Dentists and How to Prevent Them - Putri Ariyani, Annisaa; Zahrein Amalia, Aurel; Sulistyowati, Indrani; Anggraini, Wita; Yoshua Andika, Steve (Jurnal Kedokteran Gigi Terpadu, 2025)
Musculoskeletal disorders (MSDs) are pathological conditions that affect various structures of the musculoskeletal system, including nerves, tendons, muscles, joints, ligaments, and bones. MSDs are common among dentists, with the highest complaints at the neck, shoulders, back, and hands. Musculoskeletal disorders can be caused by a variety of risk factors, and posture while performing dental care procedures is one of them. The prolonged awkward posture performed by the dentist may increase the risk of MSDs. Neck pain, lower back pain (LBP), and carpal tunnel syndrome (CTS) are the most common types of MSDs suffered by dentists. A study revealed that dentists are experiencing lost productivity due to MSDs, caused by musculoskeletal complaints, poor sleep quality, and high stress levels. Therefore, the understanding and implementation of ergonomic principles in dentistry is important for the prevention of MSDs. The use of dental loupes, stretching, and regular exercise can also help maintain the productivity of dentists.